Pengaturan Hukum Petisi Online Sebagai Kebebasan Berpendapat Terhadap Penyelenggaraan Pemerintahan - Nurul Safitri; Jantje Tjiptabudy; Hendry John Piris (Faculty of Law, Universitas Pattimura, 2022)
Introduction: People are getting smarter at using the existing media to exercise their right to express opinions, one of which is through online petitions.Purposes of the Research: to find out the legal arrangements and the implications of online petitions on governance. Methods of the Research: This research is a normative legal research. In this study, three approaches to the problem are used, namely the statutory approach, the conceptual approach, and the comparative approach. Sources of data obtained are primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials is by collecting and grouping them according to their respective parts, both primary, secondary and tertiary laws. All data in this study were analyzed qualitatively. Results / Findings / Novelty of the Research : The results of this study identified that online petitions are electronic mails that are currently popular among the public. However, Indonesia does not yet have specific regulations regarding online petitions. The implications obtained from the online petition platform are able to facilitate as well as involve citizens in voicing their opinions and actively in carrying out the role of citizens by implementing direct democracy, namely the community participating in public management.